Analysis of the amount of lost fluids, some blood components and mineral salts in volleyball under hot weather conditions - Huda Badwi Shbeeb; Suhad Qasim Saeed Almousawi; Sundus Mousa Jawad (Universidad de Murcia, 2023)
The research objective was to study the amount of lost fluids, some blood components and mineral salts in volleyball players under hot weather conditions. The sample of the present study was composed of 12 volleyball players of Al-Sinaa Club (Baghdad, Iraq) in the 2022/2023 season. The variables analyzed in this study were: Heart rate before and after exercise, internal and external body temperature before and after exertion, potassium ion, sodium ion, calcium ion, and the amount of fluid lost (the player's weight) before and after the exercise. The tests were conducted at a temperature between 42-47 degrees Celsius. The maximum anaerobic exercise was performed with volleyball. The results showed that to play volleyball under hot weather conditions (42-47 degrees Celsius) significantly increased the following variables in volleyball players: heart rate, external body temperature, internal body temperature, sodium ion and calcium ion. However, potassium ion significantly decreased. Therefore, training in hot weather has positive physical repercussions. The authors recommend to train in different weather conditions.